TORAKOCHIRUGIADeposits of mercury in the lung tissue after suiside attempt – a case report - Wójcik, Norbert; Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
A case of 40-year-old man with left pneumothorax treated by drainage is described. There were numerous deposits of mercury in both lungs after suicide attempt performed by intravenous administration 10 years ago. The deposits of mercury were wide spread in the lungs in accordance with lung vascular bed anatomy.